2014
DOI: 10.1007/s11524-013-9859-y
|View full text |Cite
|
Sign up to set email alerts
|

Bedbug Complaints among Public Housing Residents—New York City, 2010–2011

Abstract: Few studies have evaluated population-level risk factors for having a bedbug infestation. We describe characteristics associated with bedbug complaints among New York City Housing Authority (NYCHA) residents. Unique households receiving bedbug extermination services in response to a complaint during January 1, 2010 to December 31, 2011 were identified from NYCHA's central facilities work order database. We examined associations between household characteristics and having a bedbug complaint using a generalized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
16
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 13 publications
4
16
2
Order By: Relevance
“…The common bed bug, Cimex lectularius L. (Hemiptera: Cimicidae), has become a common pest in low-income housing in North America in recent years. [1][2][3][4][5] Unlike other common household pests, bed bug bites can cause itchiness, pain, anxiety, sleep loss, social ostracism, delusional parasitosis, and stress. [6][7][8][9] Professional bed bug control service typically costs at least US $500 per infestation and often fails to completely eradicate the bed bugs.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The common bed bug, Cimex lectularius L. (Hemiptera: Cimicidae), has become a common pest in low-income housing in North America in recent years. [1][2][3][4][5] Unlike other common household pests, bed bug bites can cause itchiness, pain, anxiety, sleep loss, social ostracism, delusional parasitosis, and stress. [6][7][8][9] Professional bed bug control service typically costs at least US $500 per infestation and often fails to completely eradicate the bed bugs.…”
Section: Introductionmentioning
confidence: 99%
“…A few field studies focusing on bed bug IPM in low-income apartments were carried out in response to the growing prevalence of bed bug infestations. These studies showed that: (1) using bed bug interceptors is more cost-effective, and more accurate, than using trained dogs or visual inspection 10,13 for detecting new infestations and evaluating control effectiveness; (2) heavy infestations take significantly more time and require more treatments to eliminate compared with light infestations; 11 (3) non-chemical methods alone can eliminate light infestations; 14,15 (4) continuous monitoring for 4-6 weeks beyond perceived absence of bed bugs is necessary to confirm elimination; 11 and (5) periodic building-wide inspections are necessary for identifying new infestations. 1,16,17 Currently, most housing authorities in the USA use low-bid, low-quality, contracted pest control services that often suppress the bed bug population but fail to eliminate the infestation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, recent attempts to do so have been limited in spatial extent (Hwang et al, 2005), have focused on narrow strata of socioeconomic condition (Cooper, Wang, & Singh, 2016;Gounder, Ralph, Maroko, & Thorpe, 2014;Wang, Saltzmann, & Chin, 2010), and are based on self-reported data (Ralph, Jones, & Thorpe, 2013) that are subject to known associated biases (Brown, Kelly, & Whitall, 2014).…”
mentioning
confidence: 99%
“…According to WHO the increased infestation was the result of the increased international travel, the ban of some insecticides like DDT, and increased resistance of bedbugs to insecticides [2] . Studies across United State (US) have pointed highly populated areas and low income communities are vulnerable to infestation [5][6][7] . In rural settlements of Benue state Nigeria among 199 residential apartments, which were surveyed 1056 bedbugs were collected from 26 apartments while other apartments showed probable infestation and some did not show any signs of infestation [8] .…”
Section: Introductionmentioning
confidence: 99%